Perceptions of parents on satisfaction with care in the pediatric intensive care unit: The EMPATHIC study - Latour, Jos; Van Goudoever, J.; Duivenvoorden, H.; Van Dam, N.; Dullaart, E.; Albers, M.; Verlaat, C.; Van Vught, E.; Van Heerde, M.; Hazelzet, J. (Springer-Verlag, 2009)
Purpose: To identify parental perceptions on pediatric intensive care-related satisfaction items within the framework of developing a Dutch pediatric intensive care unit (PICU) satisfaction instrument. Methods: Prospective cohort study in tertiary PICUs at seven university medical centers in The Netherlands. Participants: Parents of 1,042 children discharged from a PICU. Results: A 78-item questionnaire was sent to 1,042 parents and completed by 559 (54%). Seventeen satisfaction items were rated with mean scores <8.0 (1, completely unimportant, to 10, very important) with standard deviations =1.65, and thus considered of limited value. The empirical structure of the items was in agreement with the theoretically formulated domains: Information, Care and Cure, Organization, Parental Participation, and Professional Attitude. The Cronbach's a of the domains ranged between 0.87 and 0.94. Conclusions: Parental perceptions on satisfaction with care measures were identified and prioritized. Reliabilities of the items and domains were of high level.